GENETIC POLYMORPHISMS OF CRISP2 GENE IN ASSOCIATION WITH INFERTILITY IN IRAQI PATIENTS - Zaid A. H; Abdulkareem A. Al-Kazaz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The objective of this study was to evaluate the association and effect of CRISP2 variants on the risk of asthenozoospermia, a male infertility condition marked by absent or diminished sperm motility. There are numerous reasons why individuals develop asthenozoospermia. Therefore, it is crucial to understand the molecular mechanisms underlying this condition of infertility. Furthermore, seminal plasma, a rich source of sperm quality-related biomarkers, transports the many spermatozoa pools that make up human ejaculate down the epididymis. These spermatozoa vary in size, shape, and motility. The morphology and mobility of male ejaculated spermatozoa are affected by a number of genes, including CRISP2. In seminal samples from 120 Iraqi infertile male patients and 40 healthy males who were matched for age, gender, and ethnicity as a control group, the connection of the CRISP2 gene single nucleotide polymorphisms L56V, M176I, and C196R with infertility was investigated. According to statistical analysis of the genotype distribution of these three nsSNPs of the CRISP2 gene in patients with the asthenozoospermia subgroup and the control group, there weren’t detectable differences in genotype distribution between AS, OAS, OTA, and fertile men in the Iraqi research sample. Based on allele frequencies, C, T, and G were determined to be protective alleles, with OR values of 0.74, 0.64, and 2.0, respectively.